Implementation of Differentiated Learning with Loose Part Media to Foster Critical Reasoning Skills and Literacy in 4-5 Year Old Children - Setiawati, Erni; Fitri, Ruqoyyah; Sukartiningsih, Wahyu (Murhum : Jurnal Pendidikan Anak Usia Dini, 2024)
The importance of the early childhood phase as a foundation for child development is the main basis for designing this learning approach. Children at an early age, who are full of curiosity and imagination, need a learning environment that stimulates their creativity and critical thinking. This study aims to determine the implementation of differentiated learning with loose parts media in 4-5-year-old children and its effects on their creativity, critical thinking skills, and early literacy. A qualitative approach with a case study research design was used in this study. Participants included 4-5-year-old children and their teachers. Data were collected through observations, interviews, and documentation. Data analysis involved collecting data, presenting data, and drawing conclusions. The results showed an increase in children's active participation and creativity during learning using loose parts media. Differentiation effectively supported children's individual needs and ability levels. Children engaged in discussion and collaboration, creating ideal conditions for the development of their critical thinking skills. The use of loose parts media also proved effective in introducing early literacy concepts. This research contributes to the understanding of the importance of a loose parts-based approach in forming the basis for meaningful learning in early childhood.